Punjabi Village in Pakistan. - Eglar, Zekiye (New York, 1960)
This is a study of village life in the Punjab. The people studied are Muslims, and the locus of the study is the village of Mohla, in Gujrat district, the neighboring villages which, together with Mohla, form a loosely organized cluster, and a few more distant villages which are linked to Mohla mainly through ties of marriage. Emphasis is placed on one of the institutions important in the traditional life of the village people vartan bhanji, a complex mechanism for the exchange of gifts and services-which has served as a principal means of integration in this society.
Keywords: Villages .